Effect of Tomato Pomace Addition on Chemical, Technological, Nutritional, and Sensorial Properties of Cream Crackers - Gjore Nakov; Andrea Brandolini; Lorenzo Estivi; Katia Bertuglia; Nastia Ivanova; Marko Jukić; Daliborka Koceva Komlenić; Jasmina Lukinac; Alyssa Hidalgo (Antioxidants, 2022)
The aim of this research was to determine the influence of tomato pomace (TP) addition on the chemical, nutritional, and technological characteristics of cream crackers made from wheat flour and 4%, 6%, 8%, and 10% TP. The TP-enriched cream crackers showed progressively increasing ash (from 0.69 of the control to 1.22 g/100 g dry matter of the 10% TP sample), fat (from 11.39 to 13.04 g/100 g), protein (from 13.53 to 15.60 g/100 g), total dietary fibre (from 4.08 to 7.80), carotenoids (from 0.55 to 8.56 mg/kg), tocols (from 57.59 to 71.63 mg/kg), free phenolic acids (from 100.08 to 277.37 mg/kg), free flavonoids (from 0.0 to 45.28 mg/kg), bound flavonoids (from 0.0 to 27.71 mg/kg), and fatty acids contents, antioxidant activity and dough viscosity. The colour coordinates increased via augmenting the amounts of TP. Thickness, volume, and specific volume decreased gradually with increasing TP; the enrichment reduced cracker hardness from 65.42 N (control) to 26.28 N (crackers with 10% TP), while the snapping force rose. Cream crackers with 8% TP showed the best sensory quality. Tomato pomace addition improves the nutritional quality of foods; furthermore, its recycling will help to solve the problems linked to the disposal of this industry waste.